Impaired Antibody-Independent Immune Response of B Cells in Patients With Acute Dengue Infection - Upasani, Vinit; Vo, Hoa Thi My; Ung, Sivlin; Heng, Sothy; Laurent, Denis; Choeung, Rithy; Duong, Veasna; Sorn, Sopheak; Ly, Sowath; Rodenhuis-Zybert, Izabela A.; Dussart, Philippe; Cantaert, Tineke (Frontiers in Immunology, 2019)
Dengue is a mosquito-borne viral disease caused by dengue virus (DENV). The disease is endemic to more than 100 countries with 390 million dengue infections per year. Humoral immune responses during primary and secondary DENV infections are well investigated. However, the impact of DENV infection on B cell subsets and their antibody-independent functions are not well documented. Through this study, we aimed to define the distribution of B cell subsets in the acute phase of DENV infection and characterise the effect of DENV infection on B cell functions such as differentiation into memory and plasma cells and cytokine production. In our cohort of Cambodian children, we observed decreased percentages of CD24hiCD38hi B cells and CD27- naïve B cells within the CD19 population and increased percentages of CD27+CD38hiCD138+ plasma cells as early as 4 days post appearance of fever in patients with severe dengue compared to patients with mild disease. Lower percentages of CD19+CD24hiCD38hi B cells in DENV-infected patients were associated with decreased concentrations of soluble CD40L in patient plasma and decreased platelet counts in these patients. In addition, CD19+CD24hiCD38hi and CD19+CD27- B cells from DENV-infected patients did not produce IL-10 or TNF-α upon stimulation in vitro suggesting their contribution to an altered immune response during DENV infection. In addition, CD19+CD27- naïve B cells isolated from dengue patients were refractory to TLR/anti-IgM stimulation in vitro, which correlated to the increased expression of inhibitory Fcγ receptors (FcγR) CD32 and LILRB1 on CD19+CD27- naïve B cells from DENV-infected patients. Collectively, our results indicate that a defective B cell response in dengue patients may contribute to the pathogenesis of dengue during the early phase of infection.